Changes in shooting accuracy among basketball players under fatigue: a systematic review and meta-analysis - Shuairan Li; Yuanyuan Luo; Yuanyuan Luo; Yingying Cao; Feng Li; Haodong Jin; Jing Mi (Frontiers in Physiology)
ObjectiveTo investigate the influence of physical and mental fatigue of different intensities (mild, moderate or severe) on basketball shooting accuracy, with the aim of informing more effective training protocols and competition strategies.MethodsLiterature searches were conducted on Web of Science, PubMed, and EBSCO databases up to 25 June 2024. Inclusion and exclusion criteria were specified, and data extraction sheets were prepared. Study quality was assessed by using the Cochrane Risk of Bias Tool in Review Manager 5.4, and Stata18.0 software was used for heterogeneity analysis, subgroup analysis, forest plots, stratification analysis, and bias assessment.ResultsModerate physical fatigue affected two-point shooting accuracy (P < 0.01),severe physical fatigue affected both two-point (P = 0.02) and three-point shooting accuracy (p < 0.01),with severe physical fatigue showing a greater detrimental impact on three-point shooting accuracy, while two-point shooting accuracy may vary under specific conditions. Additionally, adolescent athletes were less affected by severe physical fatigue compared to adult athletes or those with longer training experience. Moderate mental fatigue also significantly reduced free-throw accuracy (p < 0.01).ConclusionThe shooting accuracy of basketball players was significantly affected by moderate and severe physical fatigue. Severe physical fatigue notably adversely affected the accuracy of three-point shooting relative to moderate fatigue; Additionally, moderate mental fatigue significantly reduced free-throw accuracy, which may be attributed to a decline in cognitive executive functions, highlighting the importance of fatigue management in sports training.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/#myprospero, identifier CRD42024539553